The effect of COVID-19, Non-performing Loans, and Non-Interest Income on Bank Performance: Case Study in ASEAN-5's Banking Industry - Christina Indah; Rofikoh Rokhim (Master of Management, School of Business and Management, Petra Christian University, 2023)
The COVID-19 pandemic that has hit the entire world has also had a major impact on the banking industry at the global level. Therefore, this study aims to examine the effects of the COVID- 19 pandemic, non-performing loans, and non-interest income in ASEAN-5 countries from the first quarter of 2020 to the fourth quarter of 2021. The sample consists of 86 banks listed in the capital markets of Indonesia, Malaysia, Thailand, Singapore, and Philippines. The research method used is panel regression estimated using fixed effect model and random effect model. The results showed that COVID-19 had a significant positive effect on net income after taxes, while non-performing loans also had a significant and negative effect on banking performance. However, there is no significant role in non-interest income in banking in ASEAN-5.